2020
DOI: 10.17219/acem/112613
|View full text |Cite
|
Sign up to set email alerts
|

Palmoplantar pustulosis: Factors causing and influencing the course of the disease

Abstract: Palmoplantar pustulosis (PPP) is a chronic inflammatory disease, most often occurring in middle-aged women. In the course of the condition, painful skin lesions appear on the hands and feet, i.e., areas that are extremely important in everyday life. Therefore, the disease significantly reduces quality of life. The pathogenesis of this disease is poorly understood, although it is known that genetic, immunological and environmental factors play a role in its development. Clinical observations confirm the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…Palmoplantar pustulosis (PPP) is a variant of psoriasis affecting about 18% of psoriatic patients [50,51]. As opposed to PV, PPP is more frequently seen in females at the age of 50-70 years especially in the smokers without a positive family history [51][52][53]. In a Swedish study (1998), it was demonstrated that 8% of PPP patients had CD and 24% of whom showed raised levels of IgA AGAs [54].…”
Section: Psoriasis and Gastrointestinal Tractmentioning
confidence: 99%
“…Palmoplantar pustulosis (PPP) is a variant of psoriasis affecting about 18% of psoriatic patients [50,51]. As opposed to PV, PPP is more frequently seen in females at the age of 50-70 years especially in the smokers without a positive family history [51][52][53]. In a Swedish study (1998), it was demonstrated that 8% of PPP patients had CD and 24% of whom showed raised levels of IgA AGAs [54].…”
Section: Psoriasis and Gastrointestinal Tractmentioning
confidence: 99%
“…A PPP é uma dermatose inflamatória crónica, rara, com erupções pustulosas nas palmas ou plantas (1). Afeta principalmente mulheres e fumadores (2). Alguns autores consideram-na variante de psoríase, enquanto outros acreditam ser uma entidade distinta (2).…”
Section: Comentáriounclassified
“…Afeta principalmente mulheres e fumadores (2). Alguns autores consideram-na variante de psoríase, enquanto outros acreditam ser uma entidade distinta (2). Caracteriza-se histologicamente por hiperqueratose alternada com focos de paraqueratose e existência de células inflamatórias perivasculares.…”
Section: Comentáriounclassified
See 1 more Smart Citation
“…The eccrine gland and duct have nicotine acetylcholine receptors (nAChRs) that are stimulated by smoking, and smoking can alter nAChR expression and result in inflammation 1 . It is known that this inflammatory process begins in the acrosyringia, arising from precipitating factors such as focal infection, smoking, and metal allergy 2 .…”
Section: Introductionmentioning
confidence: 99%